Task complexity and pre-writing condition : exploring Malaysian L2 learners’ perceptions on argumentative writing - Siak, Bie Soh (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examined the effects of task complexity and pre-writing condition on Malaysian L2 learners’ perceptions of their argumentative writing concerning their perceived task difficulty, stress, confidence to perform the task, interest in the task, and motivation to complete the task. It investigated whether the dyadic and triadic pre-writing conditions for peer discussion modulate the effects of task complexity on L2 learners’ perceptions of willingness to participate in the task and learning opportunities. In a repeated-measures design, 36 Malaysian university students performed six simple and complex argumentative writing tasks in different pre-writing conditions: individual, dyadic, and triadic.A set of questionnaires that collects L2 learners’ perceptions was administered to participants upon task completion.Repeated-measures ANOVA revealed that while cognitively more complex writing tasks directly weighed on L2 learners’ cognitive and affective domains as predicted by the Cognition Hypothesis, the pre-writing task condition with the dyadic peer discussion before the individual writing modulated their perceptions towards the complex writing task. A T-test revealed that the dyadic pre-writing task condition prompted L2 learners to be more confident and willing to participate in the task. Learners perceived performing the subsequent individual argumentative writing tasks as easier, more relaxing, more interesting, and more motivating. Practising educators may sequence class tasks based on the principle of natural progression in building learners' confidence to attempt the tasks. The dyadic peer discussion as the pre-writing condition strengthens learners' cognitive and affective domains for individual writing tasks.